PELATIHAN TERAPI KOMPLEMENTER SEBAGAI UPAYA KEMANDIRIAN ALUMNI PRODI KEPERAWATAN MASOHI POLTEKKES MALUKU - Nur Baharia Marasabessy; La Syam Abidin; Sitti Johri Nasela (Jurnal Abdimas Bina Bangsa, 2023)
Every year in Indonesia at least 10,000 new D-III nurse graduates compete for job vacancies in hospitals, with an absorption of less than 50%. The problem was found that graduates of the Masohi Nursing Study Program at the Maluku Health Polytechnic, most of them had not worked in hospitals or health centers on the grounds that the monthly salary they received did not match their daily expenses, waiting for the selection to open for Candidates for State Civil Apparatus (ASN). The absorption capacity of graduates until 2020 only reaches 40%. Complementary therapy is known as traditional therapy which is combined in modern medicine which is also known as holistic medicine. The method of implementing the activity is training and assistance in therapeutic practice. The procedure for carrying out activities starts from surveys and participant observations, surveys of community needs for acupressure and cupping therapy, training preparation, training implementation, application and participant assistance as well as activity evaluation. Through this program, graduates or trainees are expected to be able to become independent entrepreneurs in the field of nursing